Flexible and Modular Syntheses of Enantiopure 5-cis-Substituted Prolinamines from l-Pyroglutamic Acid - Prause, Felix; Kaldun, Johannes; Arensmeyer, Benjamin; Wennemann, Benedikt; Fröhlich, Benjamin; Scharnagel, Dagmar; Breuning, Matthias (Synthesis, 2015)
A wide range (25 examples) of 5-cis-substituted prolinamines is prepared in five to ten steps starting from cheap l-pyroglutamic acid. Three routes, differing mainly in the order of introduction of the substituents at the 5-cis position, the pyrrolidine nitrogen atom, and the exocyclic amino function, are successfully developed.
Keywords: amines; ligands; stereoselective synthesis; pyrrolidines; prolinamines